A method for handling the extrapolation of solid crystalline phases to temperatures far above their melting point. (March 2020) - Sundman, Bo; Kattner, Ursula R.; Hillert, Mats; Selleby, Malin; Ågren, John; Bigdeli, Sedigheh; Chen, Qing; Dinsdale, Alan; Hallstedt, Bengt; Khvan, Alexandra; Mao, Huahai; Otis, Richard
Abstract: Thermodynamic descriptions in databases for applications in computational thermodynamics require representation of the Gibbs energy of stable as well as metastable phases of the pure elements as a basis to model multi-component systems. In the Calphad methodology these representations are usually based on physical models. Reasonable behavior of the thermodynamic properties of phases extrapolated far outside their stable ranges is necessary in order to avoid that they become stable just because these properties extrapolate badly. This paper proposes a method to prevent crystalline solid phases in multi-component systems to become stable again when extrapolated to temperatures far above their melting temperature.